Rotationally driven VHE emission from the Vela pulsar - Osmanov, Zaza; Rieger, Frank M. (Astronomy and astrophysics, 2019)
Context: The recent detection of pulsed γ-ray emission from the Vela pulsar in the ∼10 to 100 GeV range by H.E.S.S. promises important potential to probe into the very high energy (VHE) radiation mechanisms of pulsars. Aims: A combined analysis of H.E.S.S. and Fermi-LAT data suggests that the leading wing of the P2 peak shows a new, hard gamma-ray component (with photon index as hard as Γ ∼ 3.5), setting in above 50 GeV and extending beyond 100 GeV. We study these findings in the context of rotationally driven (centrifugal) particle acceleration. Methods: We analyze achievable particle energies in the magnetosphere of the Vela pulsar and calculate the resultant emission properties. Results: Inverse Compton up-scattering of thermal photons from the surface of the star is shown to lead a pulsed VHE contribution reaching into the TeV regime with spectral characteristics compatible with current findings. If confirmed by further observations this could be the second case where rotationally driven processes turn out to be important to understand the VHE emission in young pulsars.
Gesehen am 05.08.2019